The TP53 Arg72Pro polymorphism predicts visual and neurodegenerative outcomes in retinal detachment - Nadia Galindo-Cabello; Eva M. Sobas-Abad; Rebeca Lapresa; Jesús Agulla; Ángeles Almeida; Antonio López; José Carlos Pastor; Salvador Pastor-Idoate; Ricardo Usategui-Martín (Cell Death and Disease)
Abstract Retinal detachment (RD) separates the retina from the retinal epithelium, causing photoreceptor apoptosis and irreversible vision loss. Even with successful surgical reattachment, complete visual recovery is not guaranteed. The TP53 Arg72Pro polymorphism, implicated in apoptosis, has emerged as a potential predictor of RD outcomes. We investigated the impact of the Arg72Pro polymorphism on retinal neurodegeneration and functional recovery in patients. The underlying mechanisms were analyzed in a humanized TP53 Arg72Pro RD mouse model. In a cohort of 180 patients, carriers of the Pro allele exhibited decreased apoptotic gene expression and improved visual recovery. Complementary findings in mice revealed that the Pro variant preserved photoreceptor integrity and reduced apoptosis rates following RD. Our findings highlight the potential of this TP53 polymorphism as a biomarker for RD outcomes and a tool for tailoring therapies. This study underscores the importance of integrating genetic profiling into personalized medicine approaches to improve recovery of RD patients’ visual outcomes.